Level of Understanding and Perception of SIPSS Registrants from the Department of Law Related to Criminology Materi - Endro Tri Susdarwono (Indonesian Journal of Police Studies, 2022)
Crime is a complex phenomenon that can be understood from many different perspectives. This study aims to examine the level of understanding and perception of SIPSS applicants from the Department of Law related to Criminology material. The approach used in this research is descriptive quantitative. The data collection technique used a questionnaire with purposive sampling type, while for the technique in analyzing the data applied hypothesis testing on the analysis of variance through Friedman's two-way level. Data analysis using analysis of variance through the two-way Friedman level was applied to determine whether or not there were significant differences in values ​​in several population groups. Through this method, the sample data is arranged in a two-way table consisting of a number of rows and columns. This study concludes that the respondents have significant differences in preferences for the four models of explanations for crime. In this condition, registrants for the Source Police Inspector School (SIPSS) from the Department of Law have a certain tendency to understand the process of a crime based on the perspective they choose and they believe as the basis for understanding in explaining crime.